Peran Guru dalam Meningkatkan Akhlak Mulia Siswa MAN 3 Banyuwangi - Rahmat, Muhammah Ade Jalaludin; Syahid, Mar; Fitria, Mulajimatul (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2023)
This study aims to evaluate the role of Islamic Religious Education (PAI) teachers in fostering and improving students' morals at MAN 3 Banyuwangi and the coaching approach used. The method used in this study is qualitative with in-depth interview techniques involving teachers, principals, and students. This study identifies the role of teachers as leaders, role models, facilitators, and motivators who contribute to fostering students' morals. The results of the interviews showed that the approaches applied include exemplary examples, advice, special attention, habituation, and punishment. These approaches have been applied consistently and effectively, and in accordance with existing theories about moral development. Teachers at MAN 3 Banyuwangi have succeeded in integrating theory and practice in the process of moral education by providing good examples, providing constructive advice, paying special attention to students, as well as getting used to good behavior and implementing educational punishments. All practices applied show consistency with the theory put forward about the role and methods of moral development. This study concludes that teachers' efforts in moral education at MAN 3 Banyuwangi are effective and have a positive impact on the formation of students' character. Suggestions for future research include deepening the study of the long-term impact of the coaching method and further evaluation of the implementation of the method in other contexts.